Komma hemifrån: Geografi och identitet i unga semestrares thailandsbloggar - Berg, Magnus (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2010)
The article discusses the expansion of the concept of "home" as a consequence of modern, long-range tourism. The material consists of fifteen blogs written by young Swedish travelers who have visited some of the most popular tourist destinations in Thailand for a shorter period of time. The blogs construct a sort of familiarization of contexts situated far away from Sweden which incorporates them with the idea of "home". The communication in the blog shows that journeys do not go to Thailand itself, understand as a specific and non-Swedish historical, economic and social context about which the blogs has close to nothing to say. Instead the blogs are exclusively focused on the "tourist zone" in Thailand. The tourist zone is a context constructed only to meet the tourist's demand for leisure, relaxation and hedonism. It is therefore a generalized zone that could be found on many places outside Thailand. Familiarity, and the ongoing process of education to familiarity, with the tourist zone in Thailand appears as a training in Sweden normality. In that sense Thailand, or rather a very peculiar version of Thailand, could be said to be incorporated with everyday life in Sweden. The theoretical sources of the article are of postcolonial and critical tourism research origin.